Cross-linked polymer as well as preparation method and application thereof

By introducing structural units A, B, C and crosslinking units into the anti-high temperature viscosity enhancer, and cross-linking with dihaloalkanes to form a cross-linked polymer with a three-dimensional network structure, the high temperature resistance and high temperature resistance in the prior art are solved The problem of the failure of viscosity enhancer under salt conditions has achieved efficient viscosity enhancement and salt resistance at 180°C.

CN119219824AActive Publication Date: 2024-12-31CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310771111.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

The existing high-temperature viscosity-enhancing agents fail under high-temperature and high-salt conditions, making it difficult to take into account both viscosity-enhancing performance, high-temperature and salt-resistant properties.

Method used

Crosslinking polymers containing structural units A, B, C and crosslinking units are used to crosslink through dihaloalkane crosslinking agent to form a product with a three-dimensional network structure, enhancing the resistance to mild salt resistance.

Benefits of technology

The good viscosity-enhancing effect is maintained at 180°C, and the performance in the anti-NaCl and anti-CaCl2 saturated solutions is significantly improved, and the stability of the molecular chain is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219824A_ABST
    Figure CN119219824A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of oilfield chemistry, in particular to a cross-linked polymer and a preparation method and application thereof. The cross-linked polymer comprises a structural unit A, a structural unit B, a structural unit C and a cross-linking unit, wherein the structural unit A is # imgabs 0 #, the structural unit B is # imgabs 1 #, the structural unit C is # imgabs 2 #, M represents a metal combined with a phosphonic acid group in an ionic bond form, and m is the valence state of M. By optimizing a cross-linking system, the obtained random terpolymer can significantly improve the viscosity retention rate of the cross-linked polymer at high temperature, can enhance the salt resistance (NaCl saturation resistance and CaCl2 saturation resistance), and also has good rock-carrying performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemistry, and in particular to a cross-linked polymer and a preparation method and application thereof. Background Art

[0002] The drilling depth in my country has reached 9,000 meters, with bottom hole temperatures ranging from 180 to 260°C, and large sections of salt-gypsum layers in most areas. As the exploration field extends to deeper formations, the formations being drilled become more and more complex, with an increase in high-temperature, high-pressure, and high-salt formations. This places higher demands on the performance of drilling fluid treatment agents.

[0003] Viscosity enhancers are a type of treatment agent used in large quantities in drilling and completion fluids. They are usually made of polymers and are characterized by long molecular chains and good water solubility. In addition to their viscosity-enhancing effects, viscosity enhancers are often used as shale inhibitors (coating agents), fluid loss reducers, and flow pattern improvers. Therefore, the use of viscosity enhancers is often beneficial to improving the rheology of drilling fluids and is also beneficial to well wall stability.

[0004] In the prior art, CN102127401A discloses a high temperature resistant thickener for drilling fluid and a preparation method thereof, which is prepared by mixing starch, guar gum, alkaline hydroxide, epoxide and alcohol solvent in a certain proportion, and then stirring, drying, crushing and other processes. The temperature resistance of the product in freshwater drilling fluid can reach 150°C, and the temperature resistance in seawater drilling fluid can reach 140°C. CN101955564A discloses a preparation method for a high temperature resistant and salt resistant thickener for drilling fluid, which is prepared by aqueous solution polymerization using 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid and acrylamide as raw materials. The thickener has good stability at a formation temperature of 150°C and still has a certain effect in a 10% brine solution. CN104293325A discloses a viscosity reducer for drilling fluid and a preparation method thereof, which introduces acrylic acid, a sulfonating agent, a cationic monomer and an organic phosphonate into a reaction system, can effectively reduce the viscosity of high-density polymer drilling fluid, and still maintain good viscosity reduction performance at a high temperature of 200°C. However, its optimization direction is viscosity reduction, and there is still room for further improvement while taking into account viscosity-increasing performance, high temperature resistance and salt resistance.

[0005] It can be seen that the temperature resistance of domestic high temperature resistant viscosity enhancer products is usually around 150-180℃, and when the system mineralization is high (especially Ca 2+ Concentration higher than 1.4×10 4 mg / L), the viscosity enhancer will have molecular chain curling and winding, resulting in product failure. Conventional aqueous solution polymerization methods have certain limitations. This field is in urgent need of developing a viscosity enhancer product that can still maintain good performance under high temperature and high salt conditions. Summary of the invention

[0006] The purpose of the present invention is to provide a cross-linked polymer and a preparation method and application thereof, so as to overcome the defects in the prior art that it is difficult to balance the viscosity increasing performance, high temperature resistance and salt resistance, and realize a cross-linked polymer that can still have a good viscosity increasing effect at 180°C, can resist NaCl saturation, and can resist CaCl 2 Saturated cross-linked polymer.

[0007] In a first aspect, the present invention first provides a cross-linked polymer, which includes a structural unit A, a structural unit B, a structural unit C and a cross-linking unit;

[0008] Among them, the structural unit A is The structural unit B is The structural unit C is

[0009] Wherein, M represents a metal bonded to the phosphonic acid group in the form of an ion bond, and m represents the valence state of M.

[0010] The present invention unexpectedly discovered that the molecular structure containing the above-mentioned structural units can effectively increase the temperature resistance of the product and adjust the rheological properties of the drilling fluid system; at the same time, the combination of carboxylic acid groups and phosphonic acid groups can enhance the water solubility of the cross-linked polymer and reduce the hydration time; the introduction of phosphonic acid groups and the increase in the polarity of the salt solution lead to enhanced hydrophobic association, which can significantly improve the calcium and salt resistance of the cross-linked polymer.

[0011] Preferably, the polymerization degrees of the structural units A, B, and C are the same or different and are in the range of 2000 to 5000.

[0012] Preferably, M is a monovalent metal, a divalent metal, a trivalent metal or a tetravalent metal.

[0013] More preferably, M is one of the Group IA metals, and m is 1; further preferably, M is sodium or potassium; most preferably, M is sodium.

[0014] Or, M is one of the divalent metals, and m is 2; further preferably, M is selected from one or more of magnesium, calcium, copper and iron.

[0015] Or, M is one of the trivalent metals, and m is 3; more preferably, M is iron or aluminum.

[0016] Or, M is one of the tetravalent metals, and m is 4; more preferably, M is titanium or zirconium.

[0017] Preferably, the cross-linking unit is C 1 ~C 25 of a straight chain alkyl group.

[0018] The present invention finds that when the molecular structure of the cross-linked polymer contains a carbon-carbon long chain and a ring structure, the macromolecular chain can produce intramolecular and intermolecular associations, and the hydrodynamic volume of the molecular structure increases, which can further improve the temperature resistance of the cross-linked polymer and adjust the rheological properties of the drilling fluid system.

[0019] More preferably, the cross-linking unit is C 6 ~C 10 of a straight chain alkyl group.

[0020] Preferably, the cross-linked polymer has the structural formula:

[0021]

[0022] Wherein, M represents a metal bonded to the phosphonic acid group in the form of an ionic bond, m is the valence state of M; and n represents the number of carbon atoms, 1≤n≤25.

[0023] Preferably, the content of the cross-linking unit is 0.01-0.05 wt % based on the total amount of the cross-linked polymer.

[0024] Preferably, based on the total amount of the cross-linked polymer, the content of the structural unit A is 30-60 wt %.

[0025] Preferably, based on the total amount of the cross-linked polymer, the content of the structural unit B is 25-45 wt %.

[0026] Preferably, based on the total amount of the cross-linked polymer, the content of the structural unit C is 10 to 30 wt %.

[0027] In a second aspect, the present invention further provides a method for preparing the cross-linked polymer, comprising: subjecting diallylaminomethylphosphonate, acrylic acid and N-vinylcaprolactam to inverse emulsion polymerization to obtain a polymer; and then cross-linking the polymer using a dihalogenated alkane as a cross-linking agent to obtain the cross-linked polymer.

[0028] The present invention finds that by using dihalogenated hydrocarbons as the crosslinking agent of the above reaction system, the polymerized product is further subjected to a quaternization reaction with dihalogenated hydrocarbons, and the long side chains in the phosphonic acid monomers are stably crosslinked with the carbon-carbon long chains. On the one hand, the three-dimensional network structure of the product molecules can enhance the rock-carrying performance of the product; on the other hand, the introduction of carbon-carbon long chains is conducive to increasing the molecular structure strength of the product, which can effectively enhance the temperature resistance while further inhibiting the curling of the molecular chain under high salt conditions, and the salt resistance of the product is significantly improved.

[0029] Preferably, the dihaloalkane is selected from 1,2-dichloroethane, 1,2-dichloropropane, 1,3-dichloropropane, 1,2-dichlorobutane, 1,3-dichlorobutane, 1,4-dichlorobutane, 1,2-dichloropentane, 1,3-dichloropentane, 1,4-dichloropentane, 1,5-dichloropentane, 1,2-dichlorohexane, 1,3-dichlorohexane, 1,4-dichlorohexane, 1,5-dichlorohexane, 1,6-dichlorohexane, 1,2-dichloroheptane, 1,3-dichloroheptane, 1,4-dichloroheptane, 1,5-dichloroheptane, 1,6-dichloroheptane, 1,7-dichloroheptane, 1,2 -dichlorooctane, 1,3-dichlorooctane, 1,4-dichlorooctane, 1,5-dichlorooctane, 1,6-dichlorooctane, 1,7-dichlorooctane, 1,8-dichlorooctane, 1,2-dichlorononane, 1,3-dichlorononane, 1,4-dichlorononane, 1,5-dichlorononane, 1,6-dichlorononane, 1,7-dichlorononane, 1,8-dichlorononane, 1,9-dichlorononane, 1,2-dichlorodecane, 1,3-dichlorodecane, 1,4-dichlorodecane, 1,5-dichlorodecane, 1,6-dichlorodecane, 1,7-dichlorodecane, 1,8-dichlorodecane, 1,9-dichlorodecane, 1,1 0-dichlorodecane; 1,2-diiodoethane, 1,2-diiodopropane, 1,3-diiodopropane, 1,2-diiodobutane, 1,3-diiodobutane, 1,4-diiodobutane, 1,2-diiodopentane, 1,3-diiodopentane, 1,4-diiodopentane, 1,5-diiodopentane, 1,2-diiodohexane, 1,3-diiodohexane, 1,4-diiodohexane, 1,5-diiodohexane, 1,6-diiodohexane, 1,2-diiodoheptane, 1,3-diiodoheptane, 1,4-diiodoheptane, 1,5-diiodoheptane, 1,6-diiodoheptane, 1,7-diiodoheptane, 1,2-diiodooctane, 1 , 3-diiodooctane, 1,4-diiodooctane, 1,5-diiodooctane, 1,6-diiodooctane, 1,7-diiodooctane, 1,8-diiodooctane, 1,2-diiodononane, 1,3-diiodononane, 1,4-diiodononane, 1,5-diiodononane, 1,6-diiodononane, 1,7-diiodononane, 1,8-diiodononane, 1,9-diiodononane, 1,2-diiododecane, 1,3-diiododecane, 1,4-diiododecane, 1,5-diiododecane, 1,6-diiododecane, 1,7-diiododecane, 1,8-diiododecane, 1,9-diiododecane, 1,10-diiododecane;1,2-dibromoethane, 1,2-dibromopropane, 1,3-dibromopropane, 1,2-dibromobutane, 1,3-dibromobutane, 1,4-dibromobutane, 1,2-dibromopentane, 1,3-dibromopentane, 1,4-dibromopentane, 1,5-dibromopentane, 1,2-dibromohexane, 1,3-dibromohexane, 1,4-dibromohexane, 1,5-dibromohexane, 1,6-dibromohexane, 1,2-dibromoheptane, 1,3-dibromoheptane, 1,4-dibromoheptane, 1,5-dibromoheptane, 1,6-dibromoheptane, 1,7-dibromoheptane, 1,2-dibromooctane, 1,3-dibromooctane, Bromooctane, 1,4-dibromooctane, 1,5-dibromooctane, 1,6-dibromooctane, 1,7-dibromooctane, 1,8-dibromooctane, 1,2-dibromononane, 1,3-dibromononane, 1,4-dibromononane, 1,5-dibromononane, 1,6-dibromononane, 1,7-dibromononane, 1,8-dibromononane, 1,9-dibromononane, 1,2-dibromodecane, 1,3-dibromodecane, 1,4-dibromodecane, 1,5-dibromodecane, 1,6-dibromodecane, 1,7-dibromodecane, 1,8-dibromodecane, 1,9-dibromodecane, 1,10-dibromodecane; 1,2-difluoroethane, 1,2-difluoropropane, 1,3-difluoropropane, 1,2-difluorobutane, 1,3-difluorobutane, 1,4-difluorobutane, 1,2-difluoropentane, 1,3-difluoropentane, 1,4-difluoropentane, 1,5-difluoropentane, 1,2-difluorohexane, 1,3-difluorohexane, 1,4-difluorohexane, 1,5-difluorohexane, 1,6-difluorohexane, 1,2-difluoroheptane, 1,3-difluoroheptane, 1,4-difluoroheptane, 1,5-difluoroheptane, 1,6-difluoroheptane, 1,7-difluoroheptane, 1,2-difluorooctane, 1,3-difluorooctane, Fluorooctane, 1,4-difluorooctane, 1,5-difluorooctane, 1,6-difluorooctane, 1,7-difluorooctane, 1,8-difluorooctane, 1,2-difluorononane, 1,3-difluorononane, 1,4-difluorononane, 1,5-difluorononane, 1,6-difluorononane, 1,7-difluorononane, 1,8-difluorononane, 1,9-difluorononane, 1,2-difluorodecane, 1,3-difluorodecane, 1,4-difluorodecane, 1,5-difluorodecane, 1,6-difluorodecane, 1,7-difluorodecane, 1,8-difluorodecane, 1,9-difluorodecane or 1,10-difluorodecane.

[0030] More preferably, the dihaloalkane is selected from 1,6-dibromohexane, 1,7-dibromoheptane, 1,8-dibromooctane, 1,9-dibromononane or 1,10-dibromodecane.

[0031] Preferably, the amount of the dihaloalkane is 0.1 to 0.5 wt‰ of the total mass of diallylaminomethylphosphonate, acrylic acid and N-vinylcaprolactam; specifically, the amount of the dihaloalkane can be 0.1 wt‰, 0.2 wt‰, 0.3 wt‰, 0.4 wt‰, 0.5 wt‰ of the total mass of diallylaminomethylphosphonate, acrylic acid and N-vinylcaprolactam.

[0032] Preferably, the mass ratio of the diallylaminomethylphosphonate, acrylic acid and N-vinylcaprolactam is 0.5-3:1-5:0.1-1.

[0033] Preferably, the preparation method of the cross-linked polymer comprises:

[0034] S1: mixing diallylaminomethylphosphonate, acrylic acid, N-vinylcaprolactam and water to obtain an aqueous phase;

[0035] S2: mixing an emulsifier with white oil to obtain the oil phase; then mixing the oil phase with the water phase and stirring to obtain an emulsion;

[0036] S3: mixing the emulsion with an initiator aqueous solution under a nitrogen atmosphere at a temperature of 40 to 80° C. to react to obtain a reaction solution;

[0037] S4: Under nitrogen atmosphere and temperature conditions of 40-80° C., the reaction solution is mixed with a dihalogenated alkane for reaction. After the reaction is completed, the product obtained is a cross-linked polymer.

[0038] Preferably, in S1, the mass ratio of the total mass of the diallylaminomethylphosphonate, acrylic acid and N-vinylcaprolactam to the water is (0.3-1.3):1.

[0039] Preferably, in S2, the emulsifier is selected from one or more of op10, span80 and tween60.

[0040] More preferably, the emulsifier is a composite emulsifier of span80 and op10 in a mass ratio of (5-10):1; or, the emulsifier is a composite emulsifier of span80 and tween60 in a mass ratio of (5-10):1.

[0041] More preferably, the emulsifier is used in an amount of 2 to 10 wt % of the total mass of diallylaminomethylphosphonate, acrylic acid and N-vinylcaprolactam.

[0042] Preferably, in S2, the white oil is industrial white oil; more preferably, the industrial white oil is selected from one or more of industrial white oil No. 3, industrial white oil No. 5, industrial white oil No. 7, industrial white oil No. 10, industrial white oil No. 15, industrial white oil No. 20, industrial white oil No. 22, industrial white oil No. 26, industrial white oil No. 32, industrial white oil No. 48 and industrial white oil No. 64.

[0043] Further preferably, the mass ratio of the white oil to the water in S1 is (0.8-1.2):1.

[0044] Preferably, in S3, the initiator is selected from inorganic peroxide initiators and / or azo initiators.

[0045] More preferably, the inorganic peroxide initiator includes one or more of potassium persulfate, sodium persulfate and ammonium persulfate; the azo initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azobisisobutyramidine hydrochloride and azobisisobutylimidazole hydrochloride.

[0046] More preferably, the amount of the initiator is 0.5 to 5 wt‰ of the total mass of diallylaminomethylphosphonate, acrylic acid and N-vinylcaprolactam.

[0047] In a third aspect, the present invention also provides a method for preparing the diallylaminomethylphosphonate, comprising:

[0048] S1: under contact conditions, phosphorous acid and an organic solvent are mixed, and the pH of the mixed stream is adjusted to be no greater than 7, and then diallylamine is slowly added to react to obtain a first reaction system;

[0049] S2: adding aldehyde to the first reaction system to react to obtain a second reaction system;

[0050] S3: adjusting the pH value of the second reaction system to 6-8, and then continuing the reaction, and drying the solid phase obtained by separation of the reaction product to obtain diallylaminomethylphosphonate.

[0051] Preferably, in S1, the organic solvent is selected from one or more of alcohols, esters, ethers and ketones.

[0052] More preferably, the organic solvent is selected from alcohols, esters, ethers and ketones having 1 to 12 carbon atoms.

[0053] Further preferably, the organic solvent is selected from one or more of methanol, ethanol, butanol, ethyl acetate, butyl acetate, isoamyl acetate, ethyl ether, butyl ether, acetone and methyl ethyl ketone.

[0054] Preferably, in S1, the volume ratio of the organic solvent to the phosphorous acid is 1-2:1-15, more preferably 1-2:1-8.

[0055] Preferably, in S1, the pH value of the mixed stream is adjusted to 1-6.8; more preferably, the pH value is adjusted to 1-4, and even more preferably, the pH value is adjusted to 1-3.

[0056] In the present invention, the pH value of the mixed stream in S1 is adjusted by adding an acidic substance; the acidic substance can be an inorganic acid and / or an organic acid, specifically one or more selected from hydrochloric acid, sulfuric acid, nitric acid, oxalic acid, glacial acetic acid, carbonic acid, hydrofluoric acid, citric acid, malic acid, tartaric acid and succinic acid.

[0057] Preferably, in S1, the reaction temperature is -20 to 10°C; more preferably -10 to 5°C.

[0058] Preferably, the diallylamine is added dropwise; more preferably, the addition is performed dropwise at a rate of 10 to 200 mL / h.

[0059] Preferably, in S2, the aldehyde is selected from one or more of formaldehyde, paraformaldehyde, trimeraldehyde and polyformaldehyde, more preferably formaldehyde.

[0060] Preferably, the aldehyde is added in liquid form. For example, when formaldehyde is used, it can be directly added in liquid form. When dioxymethylene, trioxymethylene, or polyoxymethylene is used, it can be first dissolved in a solvent and then added in liquid form. The solvent here can be one or more of alcohols, esters, ethers, and ketones. Further, the number of carbon atoms of the alcohols, esters, ethers, and ketones can be 1 to 12, and can be specifically selected from one or more of methanol, ethanol, butanol, ethyl acetate, butyl acetate, isoamyl acetate, ethyl ether, dibutyl ether, acetone, and methyl ethyl ketone.

[0061] Preferably, in S2, the aldehyde may be added dropwise, more preferably at a dropping speed of 10 to 200 mL / h.

[0062] Preferably, in S2, the reaction temperature is -20 to 10°C, more preferably -10 to 5°C.

[0063] Preferably, in S3, the pH value of the second reaction system is adjusted to 6-8 by adding an alkaline substance, and the alkaline substance can be an inorganic base and / or an alkaline inorganic salt. The metal in the inorganic base and / or the alkaline inorganic salt is selected from one or more of monovalent, divalent, trivalent, and tetravalent metal elements, and can be further specifically selected from one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, magnesium hydroxide, magnesium carbonate, calcium carbonate, calcium hydroxide, iron hydroxide, copper hydroxide, titanium hydroxide, zirconium hydroxide, etc., and preferably one or more of sodium hydroxide and potassium hydroxide.

[0064] Preferably, in S3, the reaction temperature is 0 to 90°C, more preferably 20 to 40°C; the reaction time is 0.5 to 6 hours, more preferably 1 to 3 hours.

[0065] Preferably, in S3, the separation is solid-liquid separation, and the solid-liquid separation can be achieved by any means that can achieve solid-liquid two-phase separation. The selection of such liquid-solid separation means is a basic skill required by technical personnel in this field, and can be reasonably selected based on actual conditions. Specifically, one or more of the methods such as filtration separation and centrifugal separation can be adopted.

[0066] Preferably, in S3, the separated liquid phase can be recycled back to S1 for continued use, and the reaction can be continued after replenishing other raw materials.

[0067] Preferably, in S3, the drying temperature is 60-120° C., and the drying time is 6-12 hours.

[0068] Preferably, the molar ratio of diallylamine, phosphorous acid and aldehyde is diallylamine:phosphorous acid:aldehyde=1:(1-2):(1-2); more preferably 1:(1-1.5):(1-1.5).

[0069] In the present invention, the entire reaction process for preparing diallylaminomethylphosphonate is carried out under anhydrous conditions.

[0070] In the present invention, an organic solvent is used as a reaction solvent in the preparation process of diallylaminomethylphosphonate, and the reaction process is carried out under anhydrous conditions, which can improve the reaction efficiency, reduce the occurrence of side reactions, and improve the purity of the obtained product. At the same time, diallylaminomethylphosphonate is water-soluble, and the use of an organic solvent reaction system in the preparation is conducive to the subsequent separation of the product, and only conventional separation means such as filtration or centrifugal separation are required to achieve clear separation of the product, and further drying at low temperature can obtain the target product, and the entire process is green, pollution-free, non-toxic and harmless.

[0071] In a fourth aspect, the present invention provides use of the cross-linked polymer in drilling fluid or completion fluid.

[0072] In the present invention, the cross-linked polymer can be used for oil field polymers such as viscosity increase, shear enhancement, drilling and completion, as well as water treatment, papermaking industry, fiber industry, coating industry, water absorbing materials, printing and dyeing auxiliaries, biomedicine and other fields.

[0073] Preferably, the cross-linked polymer is used as a viscosity increasing agent.

[0074] Preferably, the amount of the cross-linked polymer used in the drilling fluid when used as a viscosity enhancer is 3 to 30 g / L.

[0075] Preferably, when the cross-linked polymer is used as a viscosity enhancer, the amount used in the completion fluid is 3 to 30 g / L.

[0076] In a fifth aspect, the present invention provides a drilling fluid comprising the above-mentioned cross-linked polymer.

[0077] In a sixth aspect, the present invention provides a completion fluid comprising the above-mentioned cross-linked polymer.

[0078] Based on the above technical solution, the beneficial effects of the present invention are:

[0079] The present invention optimizes the cross-linking system to obtain a random ternary copolymer that can significantly improve the viscosity retention rate of the cross-linked polymer at high temperatures and enhance salt resistance (resistance to NaCl saturation, resistance to CaCl 2 saturated), and also has good rock carrying performance. DETAILED DESCRIPTION

[0080] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0081] Unless otherwise specified, all raw materials used in the examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.

[0082] Example 1

[0083] This embodiment provides a cross-linked polymer, the structural formula of which is as follows:

[0084]

[0085] This embodiment further provides a method for preparing the cross-linked polymer, comprising the following steps:

[0086] Add 20g acrylic acid, 10g sodium diallylaminomethylphosphonate, 2g N-vinylcaprolactam and 70g water into a flask and stir until the solution is uniform to obtain an aqueous phase. # Add white oil to a beaker, add 0.54g Span80 and 0.1g Tween60, stir evenly to obtain an oil phase. Then add the oil phase to a flask, mix with the aqueous phase, and stir thoroughly for 30 minutes to obtain an emulsion. Dissolve 0.016g potassium persulfate completely in 10g water, and mix the emulsion with an aqueous potassium persulfate solution under a nitrogen atmosphere at 45°C to react to obtain a reaction solution. When the temperature of the reaction solution drops to 45°C, add 0.0032g 1,6-dibromohexane to the reaction solution, continue the reaction for 2h, then stop the reaction, and the resulting product is a cross-linked polymer.

[0087] The preparation method of sodium diallylaminomethylphosphonate comprises the following steps:

[0088] Add 15g of phosphorous acid and 14mL of anhydrous ethanol to the reaction container in sequence, then add 6mL of concentrated sulfuric acid (98wt%) to adjust the pH value of the system to 1, then place the reaction container in an ice-water bath, and add 8.6mL of diallylamine drop by drop through a constant drop funnel, and control the addition within 45min. After the addition is complete, continue to reflux for 3h. Then add a mixture of 15g of trioxymethylene and 14mL of anhydrous ethanol to the constant drop funnel, add drop by drop and add within 40min. After the addition is complete, continue to reflux for 4h. Add 6.0g of NaOH to the system to adjust the pH value of the system to 7, and react at 20℃ for 3h. After further centrifugation by a centrifuge, the obtained solid phase material is further dried at 90℃ for 10h to obtain the target product, diallylaminomethylphosphonic acid sodium solid powder.

[0089] Example 2

[0090] This embodiment provides a cross-linked polymer, the structural formula of which is as follows:

[0091]

[0092] This embodiment further provides a method for preparing the cross-linked polymer, comprising the following steps:

[0093] Add 20g acrylic acid, 20g calcium diallylaminomethylphosphonate, 10g N-vinylcaprolactam and 73g water into a flask and stir until the solution is uniform to obtain an aqueous phase. #Add white oil to a beaker, add 2.2g Span80 and 0.3g Tween60, stir evenly to obtain an oil phase. Then add the oil phase to a flask, mix with the water phase, and stir thoroughly for 30 minutes to obtain an emulsion. Dissolve 0.05g ammonium persulfate completely in 10g water, and under a nitrogen atmosphere and 60°C, mix the emulsion with an aqueous solution of ammonium persulfate to react to obtain a reaction solution. When the temperature of the reaction solution drops to 50°C, add 0.01g 1,7-dibromoheptane to the reaction solution, continue the reaction for 2h, and then stop the reaction. The resulting product is a cross-linked polymer.

[0094] The preparation method of the calcium diallylaminomethylphosphonate is the same as that of the sodium diallylaminomethylphosphonate, except that the alkaline reagent used to adjust the pH of the system to neutral is Ca(OH) 2 .

[0095] Example 3

[0096] This embodiment provides a cross-linked polymer, the structural formula of which is as follows:

[0097]

[0098] This embodiment further provides a method for preparing the cross-linked polymer, comprising the following steps:

[0099] Add 10g acrylic acid, 30g sodium diallylaminomethylphosphonate, 10g N-vinylcaprolactam and 40g water into a flask and stir until the solution is uniform to obtain an aqueous phase. # Add 4.5g Span80 and 0.5g GOP10 to the white oil in a beaker, stir evenly to obtain an oil phase. Then add the oil phase to a flask, mix with the water phase, and stir well for 30 minutes to obtain an emulsion. Dissolve 0.25g of azobisisobutylimidazoline hydrochloride completely in 10g of water, and mix the emulsion with an aqueous solution of azobisisobutylimidazoline hydrochloride under a nitrogen atmosphere at 45°C to react to obtain a reaction solution. When the temperature of the reaction solution drops to 60°C, add 0.025g of 1,8-dibromooctane to the reaction solution, continue the reaction for 2h, stop the reaction, and the resulting product is a cross-linked polymer.

[0100] Example 4

[0101] This embodiment provides a cross-linked polymer, whose structural formula is the same as that of embodiment 1, and whose preparation method comprises the following steps:

[0102] Add 20g acrylic acid, 10g sodium diallylaminomethylphosphonate, 2g N-vinylcaprolactam and 85g water into a flask and stir until the solution is uniform to obtain an aqueous phase. #Add white oil to a beaker, add 1.4g Span80 and 0.2g Tween60, stir evenly to obtain an oil phase. Then add the oil phase to a flask, mix with the aqueous phase, and stir thoroughly for 30 minutes to obtain an emulsion. Dissolve 0.064g potassium persulfate completely in 10g water, and mix the emulsion with an aqueous potassium persulfate solution under a nitrogen atmosphere at 45°C to react to obtain a reaction solution. When the temperature of the reaction solution drops to 45°C, add 0.0032g 1,6-dibromohexane to the reaction solution, continue the reaction for 2h, then stop the reaction, and the resulting product is a cross-linked polymer.

[0103] Example 5

[0104] This comparative example provides a cross-linked polymer, and its preparation method is the same as that of Example 1, except that 1,6-dibromohexane is replaced by N,N-methylenebisacrylamide.

[0105] Comparative Example 1

[0106] This comparative example provides a cross-linked polymer, and its preparation method is the same as that of Example 1, except that the phosphonate monomer is replaced by dimethyldiallylammonium chloride.

[0107] In order to further illustrate the technical effects of the present invention, the present invention also provides effect tests of the above embodiments and comparative examples in actual applications.

[0108] Test example

[0109] The cross-linked polymers prepared in the above examples and comparative examples were evaluated for their properties as follows:

[0110] 1. Adhesion and temperature resistance test

[0111] Preparation of polymer solution: Add 3.5 g of the cross-linked polymer prepared in the example or comparative example into 350 mL of deionized water, and stir at 8000 r / min for 20 min to obtain a polymer solution sample.

[0112] Performance test: The apparent viscosity of the polymer solution was measured at room temperature using a six-speed viscometer according to the method specified in the national standard GB / T 16783.1-2006. After the measurement, the polymer solution was transferred to a high-temperature roller furnace and aged at 180°C for 16 hours. After the aging was completed, the solution temperature was cooled to room temperature and stirred at 8000r / min for 20 minutes to measure the apparent viscosity of the aged polymer solution. The apparent viscosity data before and after aging are listed in Table 1.

[0113] Table 1 Test results of polymer viscosity enhancement and temperature resistance

[0114]

[0115]

[0116] 2. Salt resistance test

[0117] Preparation of polymer saturated salt solution: At room temperature and under stirring conditions, continuously add NaCl to 350 mL of deionized water until the solution can no longer dissolve NaCl, and a saturated NaCl solution is obtained. Add 3.5 mL of polymer sample to 350 mL of saturated NaCl solution, and stir at 8000 r / min for 20 min to obtain a polymer saturated NaCl solution. 2 The solution preparation method is the same as the polymer saturated NaCl solution.

[0118] Performance test: According to the method specified in GB / T 16783.1-2006, the apparent viscosity of the polymer solution was measured at room temperature using a six-speed viscometer. After the measurement, the polymer solution was transferred to a high-temperature roller furnace and aged at 180°C for 16 hours. After the aging, the solution temperature was cooled to room temperature and stirred at 8000r / min for 20 minutes, and the apparent viscosity of the aged polymer solution was measured. 2 The apparent viscosity data of the solutions before and after aging are listed in Tables 2 and 3, respectively.

[0119] Table 2 Test results of polymer NaCl resistance

[0120]

[0121]

[0122] Table 3 Polymers resistant to CaCl 2 Performance Test Results

[0123]

[0124] From the data in Tables 1 to 3, it can be seen that the cross-linked polymer prepared by the present invention has excellent viscosity-increasing, salt-resistant and shear-reducing properties, and still has a high viscosity retention rate after aging at a high temperature of 180°C for 16 hours. The polymer can maintain good viscosity-increasing properties in a saturated salt solution, and the apparent viscosity of the solution after aging is much higher than the data in the comparative example. In addition, the shear force of the polymer aqueous solution always remains at a high level before and after aging, indicating that the cross-linked polymer prepared by the present invention has good rock-carrying performance.

[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A cross-linked polymer, characterized in that The cross-linked polymer comprises structural unit A, structural unit B, structural unit C and a cross-linking unit; Among them, the structural unit A is The structural unit B is The structural unit C is Wherein, M represents a metal bonded to the phosphonic acid group in the form of an ionic bond, and m is the valence state of M.

2. The cross-linked polymer according to claim 1, characterized in that The M is one of a monovalent metal, a divalent metal, a trivalent metal or a tetravalent metal; Preferably, M is one of the Group IA metals, and m is 1; more preferably, M is sodium or potassium; Preferably, M is one of the divalent metals, and m is 2; more preferably, M is one or more selected from magnesium, calcium, copper and iron; Preferably, M is one of the trivalent metals, and m is 3; more preferably, M is iron or aluminum; Preferably, M is one of the tetravalent metals, and m is 4; more preferably, M is titanium or zirconium.

3. The cross-linked polymer according to claim 1 or 2, characterized in that The cross-linking unit is C1 to C 25 Preferably, the cross-linking unit is C6~C 10 of a straight chain alkyl group.

4. The cross-linked polymer according to any one of claims 1 to 3, characterized in that The structural formula of the cross-linked polymer is: Wherein, M represents a metal bonded to the phosphonic acid group in the form of an ionic bond, m represents the valence state of M; and n represents the number of carbon atoms, 1≤n≤25.

5. The cross-linked polymer according to any one of claims 1 to 4, characterized in that Based on the total amount of the cross-linked polymer, the content of the cross-linked unit is 0.01-0.05 wt %.

6. The cross-linked polymer according to any one of claims 1 to 5, characterized in that Based on the total amount of the cross-linked polymer, the content of the structural unit A is 30 to 60 wt%; and / or, based on the total amount of the cross-linked polymer, the content of the structural unit B is 25 to 45 wt%; and / or, based on the total amount of the cross-linked polymer, the content of the structural unit C is 10 to 30 wt%.

7. The method for preparing a cross-linked polymer according to any one of claims 1 to 6, characterized in that: include: Diallylaminomethylphosphonate, acrylic acid and N-vinylcaprolactam are subjected to inverse emulsion polymerization to obtain a polymer; and then the polymer is cross-linked using a dihalogenated alkane as a cross-linking agent to obtain the cross-linked polymer.

8. The method for preparing a cross-linked polymer according to claim 7, characterized in that: The dihalogenated alkane is selected from one of 1,6-dibromohexane, 1,7-dibromoheptane, 1,8-dibromooctane, 1,9-dibromononane and 1,10-dibromodecane; Preferably, the dihalogenated alkane is used in an amount of 0.1 to 0.5 wt‰ of the total mass of diallylaminomethylphosphonate, acrylic acid and N-vinylcaprolactam.

9. The method for preparing a cross-linked polymer according to claim 7 or 8, characterized in that: The mass ratio of the diallylaminomethylphosphonate, acrylic acid and N-vinylcaprolactam is 0.5-3:1-5:0.1-1.

10. The method for preparing a cross-linked polymer according to any one of claims 7 to 9, characterized in that: include: S1: mixing diallylaminomethylphosphonate, acrylic acid, N-vinylcaprolactam and water to obtain an aqueous phase; S2: mixing an emulsifier with white oil to obtain the oil phase; then mixing the oil phase with the water phase and stirring to obtain an emulsion; S3: mixing the emulsion with an initiator aqueous solution under a nitrogen atmosphere at a temperature of 40 to 80° C. to react to obtain a reaction solution; S4: Under nitrogen atmosphere and temperature conditions of 40-80° C., the reaction solution is mixed with a dihalogenated alkane for reaction. After the reaction is completed, the product obtained is a cross-linked polymer.

11. The method for preparing a cross-linked polymer according to claim 10, characterized in that: In S1, the mass ratio of the total mass of the diallylaminomethylphosphonate, acrylic acid and N-vinylcaprolactam to the water is (0.3-1.3):

1.

12. The method for preparing a cross-linked polymer according to claim 10 or 11, characterized in that: In S2, the emulsifier is selected from one or more of op10, span80 and tween60; Preferably, the emulsifier is a composite emulsifier of span80 and op10 in a mass ratio of (5-10):1; or, the emulsifier is a composite emulsifier of span80 and tween60 in a mass ratio of (5-10):1; More preferably, the amount of the emulsifier is 2 to 10 wt % of the total mass of diallylaminomethylphosphonate, acrylic acid and N-vinylcaprolactam.

13. The method for preparing a cross-linked polymer according to any one of claims 10 to 12, characterized in that: In S2, the white oil is industrial white oil; Preferably, the industrial white oil is selected from one or more of No. 3 industrial white oil, No. 5 industrial white oil, No. 7 industrial white oil, No. 10 industrial white oil, No. 15 industrial white oil, No. 20 industrial white oil, No. 22 industrial white oil, No. 26 industrial white oil, No. 32 industrial white oil, No. 48 industrial white oil and No. 64 industrial white oil; Preferably, the mass ratio of the white oil to the water in S1 is (0.8-1.2):

1.

14. The method for preparing a cross-linked polymer according to any one of claims 10 to 13, characterized in that: In S3, the initiator is selected from inorganic peroxide initiators and / or azo initiators; The inorganic peroxide initiator includes one or more of potassium persulfate, sodium persulfate and ammonium persulfate; the azo initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azobisisobutyramidine hydrochloride and azobisisobutylimidazole hydrochloride; Preferably, the amount of the initiator is 0.5 to 5 wt‰ of the total mass of diallylaminomethylphosphonate, acrylic acid and N-vinylcaprolactam.

15. Use of the cross-linked polymer according to any one of claims 1 to 6 or the cross-linked polymer prepared by the preparation method according to any one of claims 7 to 14 in drilling fluid or completion fluid; preferably, the cross-linked polymer is used as a viscosity enhancer.

16. The use according to claim 15, characterized in that When the cross-linked polymer is used as a viscosity enhancer, the amount of the cross-linked polymer used in the drilling fluid or completion fluid is the same or different and is 3 to 30 g / L.

17. A drilling fluid, characterized in that: It contains the cross-linked polymer according to any one of claims 1 to 6 or the cross-linked polymer prepared by the preparation method according to any one of claims 7 to 14.

18. A completion fluid, characterized in that: It contains the cross-linked polymer according to any one of claims 1 to 6 or the cross-linked polymer prepared by the preparation method according to any one of claims 7 to 14.

Citation Information

Patent Citations

  • Method for preparing high-temperature resistant and salt resistant tackifier for drilling fluid

    CN101955564A

  • High-temperature resistance tackifier for drilling fluid and preparation method thereof

    CN102127401A

  • Viscosity reducer for drilling fluid and preparation method thereof

    CN104293325A

  • Phosphonic acid base containing polymer and application thereof as well as phosphonic acid base containing polymer drilling fluid viscosity reducer

    CN103665263A

  • Phosphonic acid-based monomer and preparation method thereof

    CN116063345A